A proposed decision rule for the timing of soccer substitutions - Myers, B. R. (Journal of Quantitative Analysis in Sports, 2012)
Managers in soccer face a critical in-game decision concerning player substitutions. While past research has investigated the overall effect of various strategy changes during the course of a match, no studies have focused solely on the crucial element of timing. This paper uses the data mining technique of decision trees to develop a decision rule to guide managers on when to make each of their three substitutes in a match. The proposed decision rule demonstrates between 38% and 47% effectiveness when followed versus 17% and 24% effectiveness when not followed based on over 1200 observations collected from some of the world`s top professional leagues and competitions.